The use of the majalla in Islamic finance in Malaysia: a preliminary study - Shuaib, Farid Sufian (2017)
The Majalla or the Majalla al-Ahkam al-Adliyyah as a codification of parts of Islamic law covers wide ranging subjects including general principles of Islamic jurisprudence and legal rules on transactions. These principles are relevant to the practice of Islamic finance. It is an interesting question to consider the impact of this Code - that entered into force in 1877 in the Ottoman – over the present day practice of Islamic law in another part of the world, namely Malaysia. This research examines the use of the Majalla in the practice of Islamic finance in Malaysia. The research employs the method of textual analysis on the sources such as legislation and case law. Apart from that, interviews are conducted with parties involved in regulating and operating Islamic finance in Malaysia. The finding of the research shows the status of the Majalla as one of the essential references in the practice of Islamic finance.